THE ROLE OF INTERNAL SERVICE QUALITY AND BENEFIT PLANS ON ORGANIZATIONAL PERFORMANCE AT REGIONAL DRINKING WATER COMPANY (PDAM) SANGIHE - Paparang, Jessica Pinkan; Rumokoy, Farlane Stevie (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Globalization changing business environment rapidly. This will affect the companies in reaching its purposes such long-term profit or sustainable profitability. Facing these conditions, the management of the companies should works better in maintaining its performance. Performance in the company is strongly influenced by human resources (HR). Therefore company needs to noticed every HR within by providing services to them. Provision of services to the HR will influence their work, that also means it will influence the company. Services for HR in a company can be financial and non-financial. Both of these are things that must be fulfilled by company in providing services to the HR. This study aims to determine the role of Internal Service Quality and Benefit Plans on Organizational Performance at PDAM Sangihe. The method used associated with the data analysis technique of Multiple Regression. The results shows the Internal Service Quality and Benefit Plans at PDAM Sangihe has a role on its Organizational Performance. It means the performance at PDAM Sangihe is running well, the strong factors are caused by two variables that are discussed in this research such as Internal Service Quality and Benefit Plans. The manager of PDAM Sangihe should maintain their performance and the entire achievement associated with enhancement the company's performance, and seek a new innovations to improve the performance of the company. Keywords : organizational performance, internal service quality, benefit plans